Involvement of NpdA, a Putative 2-Nitropropane Dioxygenase, in the T3SS Expression and Full Virulence in Ralstonia solanacearum OE1-1 - Zhang, Weiqi; Li, Jing; Tang, Yu; Chen, Kai; Shi, Xiaojun; Ohnishi, Kouhei; Zhang, Yong (Frontiers in Microbiology, 2017)
Previously, we isolated several genes that potentially affected the expression of type III secretion system (T3SS) in Ralstonia solanacearum OE1-1. Here, we focused on the rsp0316, which encodes a putative 2-nitropropane dioxygenase (hereafter designated NpdA). The deletion of npdA substantially reduced the T3SS expression and virulence in OE1-1, and the complementation with functional NpdA could completely restore its reduced T3SS expression and virulence to that of wild type. The NpdA was highly conserved among diverse R. solanacearum species and the NpdA-dependent expression of T3SS was not specific to OE1-1 strain, but not the virulence. The NpdA was important for the T3SS expression in planta, while it was not required for the bacterial growth in planta. Moreover, the NpdA was not required for the elicitation of hypersensitive response (HR) of R. solanacearum strains in tobacco leaves. The T3SS in R. solanacearum is directly controlled by the AraC-type transcriptional regulator HrpB and regulated by a complex regulation network. The NpdA affected the T3SS expression mediated with HrpB but through some novel pathway. All these results from genetic studies demonstrate that NpdA is a novel factor for the T3SS expression in diverse R. solanacearum species in medium, but specifically for the T3SS expression in strain OE1-1 in planta. And the NpdA-dependent expression of T3SS in planta plays an important role in pathogenicity of R. solanacearum OE1-1 in host plants.